Influence of counterface and environment on the tribological behaviour of polymer materials - Géraldine Theiler (Elsevier, 2021)
This paper focuses on the influence of the counterface materials on the sliding behaviour of polymer materials in hydrogen. Polyimide (PI), polyetheretherketone (PEEK) and Polytetrafluoroethylene (PTFE) materials were investigated against hardened 52100 martensitic bearing steel and 304 austenitic stainless steel with similar roughness (Ra = 0.2 μm). Results indicate that the friction and wear of PI and PEEK materials depend on the counterface material. This effect wasn't observed for PTFE composites. While the tribological performance of polyimide is better against 52100 in hydrogen, improved sliding behaviour of PEEK materials is observed with 304 counterface, particularly at higher sliding speed. Surface analyses of the transfer film reveal that the influence of the counterface is primarily related to the chemical nature of the steel for PI and to the thermal conductivity of the disc for PEEK materials.